The impact of yeast temperature pre-treatment on bioethanol from corn mash fermentation - Ho, Dac Hai Nam (2013)
For commercial corn mash to ethanol production it is known that increasing temperature can maximize ethanol yield, although care must be taken to avoid causing heat shock resulting in the death of the yeast culture. Despite the potentially negative effects of high temperature, short sub-lethal stress has been reported to procure a benefit to yeast cells. However, the effect of such yeast pre-treatment on bioethanol fermentations has not previously been investigated. In order to understand more about the effects of sub-lethal heat treatment on yeast health and performance during corn mash fermentation, the tolerance of four industrial ethanologenic yeast strains to heat stress was determined. Consequently a miniature fermentation system was developed and two of the yeast strains, displaying different responses to temperature, were subjected to a variety of heat pre-treatments and analysed for their subsequent fermentation characteristics. It was noticed that although pre-treatment of yeast cells with heat did not lead to increased levels of the anti-stress compound trehalose, typically cultures exhibited improved sugar utilisation and viability post-fermentation. In addition, for strain LAL7 this also had the effect of increasing ethanol output, while for strain Thermosacc, ethanol yield was not significantly affected. Interestingly initial experimentation had indicated that Thermosacc was more thermotolerant than LAL7 and consequently it is suggested that although ethanol yield may be increased by heat pre-treatment, it may also be determined by the individual response of different strains to stress, or combinations of stress factors.